2017
DOI: 10.21577/0103-5053.20170109
|View full text |Cite
|
Sign up to set email alerts
|

Improved Method for Preparation of Methoxy-Modified Kaolinite

Abstract: A hydrated kaolinite-methanol intercalation compound (Kaol-MeOH (hydrated)) was synthesized by utilizing kaolinite/dimethyl sulfoxide intercalation compound (Kaol-DMSO) as an intermediary, and further displacement intercalation with butyl trimethylammonium chloride (BTAC) was also carried out. The obtained samples were characterized by X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR). Results showed that the d 001 value of the Kaol-MeOH (hydrated) could be arbitrary values between 0.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Uniformly dispersed smaller particles that seem coarser were noticeable which are likely to be the presence of silt and sandy component of the clay. Similar observation has also been reported [13,15,16]. The SEM/EDX of NRK indicated that the average atomic composition in percentages are; O (66.8%), Si (17.6%), Al (14.1%) and C (1.3%).…”
Section: Morphological Characterizationsupporting
confidence: 86%
See 1 more Smart Citation
“…Uniformly dispersed smaller particles that seem coarser were noticeable which are likely to be the presence of silt and sandy component of the clay. Similar observation has also been reported [13,15,16]. The SEM/EDX of NRK indicated that the average atomic composition in percentages are; O (66.8%), Si (17.6%), Al (14.1%) and C (1.3%).…”
Section: Morphological Characterizationsupporting
confidence: 86%
“…The bands at 1099 and 1006 cm -1 correspond to Si-O-Si group. The band at 694 cm -1 is due to the bending mode of the same group [13,16].…”
Section: Infrared Absorption Spectra Characterizationmentioning
confidence: 99%
“…In Figure b, the vibration band intensities of the inner‐surface hydroxyl groups of DMSO‐Kaol at 3695.6 cm −1 and 3653.2 cm −1 were decreased, and two new bands at 3537.3 cm −1 and 3501.7 cm −1 were observed. These new bands indicated that new hydrogen bonds were formed since the oxygen atoms of DMSO could bond with the surface hydroxyl groups of the kaolinite . The band at 1121.4 cm −1 was attributed to the vibration of S=O, while the bands at 1318.5 cm −1 and 1428.9 cm −1 respectively belonged to the symmetric and asymmetric deformation of CH 3 .…”
Section: Resultsmentioning
confidence: 96%
“…For this reason, there are only a few varieties of small and highly polar organic micromolecules which can be used as precursors for synthesis via solvothermal reactions; examples include dimethylsulfoxide (DMSO), N-methylformamide (NMF), urea (U), aniline, hydrazine and potassium acetate. 12 Amongst these, only DMSO organic solvent has the ability to intercalate directly because of its high dipole moment. Meanwhile, methanol (MeOH) is a polar guest species 13 which can be used as a second expansion step to permit insertion; it is an effective intermediate of large, non-reactive molecules used in displacement intercalation methods.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, methanol (MeOH) is a polar guest species 13 which can be used as a second expansion step to permit insertion; it is an effective intermediate of large, non-reactive molecules used in displacement intercalation methods. 12 In this work, expansible kaolin was functionalized with cetyltrimethylammonium bromide (cationic surfactant) and triethoxy(octyl)silane (coupling agent) to transform the properties of kaolin from hydrophilic to organophilic and consequently to achieve better compatibility with non-polar matrices in the nanocomposites due to the nano-dispersion/ distribution of llers. Furthermore, the stronger interfacial interactions between the PA6 matrix and the llers led to superior properties.…”
Section: Introductionmentioning
confidence: 99%